Variation of seed lipid content among Coffea canephora varieties - Aguiar, Adriano Tosoni da Eira; Salva, Terezinha de Jesus Garcia; Fazuoli, Luiz Carlos; Favarin, José Laércio (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to investigate the variation of lipid content in beans from different varieties of Coffea canephora Pierre specie, from the Coffee Germplasm Bank, of Instituto Agronômico, Campinas, SP, Brazil. Samples of green coffee from 47 plants were analysed: Robusta (3), Kouilou or Conilon 66 (13), Apoatã (12), Guarini (8), Laurentii (7) and Bukobensis (4). Oil content was determined after a petroleum ether extraction. Results showed difference among the average lipid content in Kouilou, at 7.33% and Robusta, at 10.91%. Differences were also observed within plants from the six varieties ranging from 15.57% to 21.63%, for Apoatã and Laurentii, respectively.